THE EFFECT OF LEADERSHIP STYLE AND MOTIVATION ON TURNOVER AT HOKA-HOKA BENTO BRANCH BSD SQUARE TANGERANG - Wahadi Siamto; Windy Gustia Wardani; Laila Irawati (Yayasan Education and Social Center, 2021)
The background of this research is that, in the current era of globalization, every organization must carry out the dynamics of change. Therefore, every organization is required to be able to compete. One strategy is to have excellent and competitive human resources. Human resources are a company's most valuable, unique, purest, and unpredictable asset. Human resources are also a central factor in the management of an organization. They are the driving force of the organization in achieving and realizing the goals and objectives set. Therefore, organizational productivity is primarily determined by the productivity of the human resources concerned. Talented human resources with good performance can support business success. Incompetent human resources and poor performance are competitive problems that can put the company at a loss. The aims of this research are 1. Does leadership style affect turnover at Hoka Hoka Bento BSD Square Tangerang Branch? 2. Does motivation affect turnover at Hoka Hoka Bento BSD Square Tangerang Branch? 3. Do leadership style and motivation affect turnover at Hoka Hoka Bento Branch BSD Square Tangerang? The method that the researcher will use is a quantitative method with a descriptive and causal associative approach. This study's population and sample were determined of 33 employees or all Hoka Hoka Bento, BSD Square Tangerang Branch employees. The result of this research is that leadership style and motivation affect turnover where the practice of leadership and motivation styles among the organization's internal employees can increase turnover